Headache and Chronic Pain Syndromes The Case-Based Guide to Targeted Assessment and Treatment - Marcus, Dawn A.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2007)
Headache and Chronic Pain Syndromes provides a case-based approach to state-of-the-art evaluation and treatment of patients with common chronically painful conditions. Offering strategies for rapidly evaluating and treating pain complaints by body region, this innovative title also provides patient educational handouts that explain the diagnosis and treatment in easy-to-understand language for each condition. Tools for implementing both medication and non-medication therapies, such as exercises and relaxation techniques, are also included. Each chapter opens with typical presentations of three to five common patient scenarios, including pediatric, adult, and geriatric patients. A targeted approach for patient assessment is provided and applied to each scenario, showing how to rapidly identify important clues to distinguish among common diagnoses, including both benign and malignant causes of pain. Standard treatment regimens are then provided for each patient, along with patient-friendly educational flyers for each common pain condition. Figures and drawings help provide ready identification of these common chronic pain syndromes. Headache and Chronic Pain Syndromes offers primary care practitioners, neurologists, and orthopedists an optimal approach to the evaluation, treatment, and follow-up of chronically painful conditions.
Pain in the Head -- Pain in the Mouth -- Pain in the Neck -- Pain in the Thorax -- Pain in the Low Back -- Pain in the Hand -- Pain in the Foot -- Pain in the Abdomen -- Pain in the Whole Body -- General Chronic Pain Management Techniques.
Keywords: Medicine; Pain medicine; Medicine & Public Health; Pain Medicine; Electronic books